‘Going concern’ assumption and ‘liquidation’ assumption. The contribution of economia aziendale in historical perspective - Galassi, Giuseppe (De Computis, Revista Española de Historia de la Contabilidad., 2023)
The focus of the paper is on the income orientation (versus capital orientation) that proved to be particularly relevant in Italy during the last one hundred years in conjunction with the monetary equilibrium, an axiom of economia aziendale which helps, still nowadays in times of transmodating dynamics, to face and solve many problems, included ‘on going’ and ‘abandon’ decisions. Furthermore, the aim of research is to draw attention to the large Italian literature, often internationally unknown, hoping it can contribute to the knowledge of accounting history in different Countries and cultures. Throughout one hundred years of economia aziendale it has not been possible to split various periods in which more emphasis is on the assumption of ‘going concern’ or on the assumption of ‘liquidation’, because the different Authors refer systematically and continuously to both hypotheses in a joint economic connection. The ‘going concern’ hypothesis is referred to every ‘economic unit’, azienda in Italian literature. The contemporary overall crisis involves accounting statutory regulations and standard setters, debating prospective conditions of concern continuity, which is the economic, financial, monetary, patrimonial and general synergic equilibrium, as well as the connected social, political, anthropological, environmental, sustainability aspects. The accent is on income flows magnitudes in order to ‘on going’ or ‘wave’ decision. In this way, also ‘money and credit’ dynamics is interpreted in the aspects of income production, the maintaining of ‘monetary equilibrium’, and the control of capital structure. In this regard the income concept, in different configurations, is a fundamental unavoidable construction, especially economic income, which tends to move the determination to decisions and implementing actions, also in most adverse situations, considering in the decision process all the variables which explicitly reflect the azienda, concern, in its unitary, dynamic, continuum system. Hence, the constant control over ‘production conditions’ and also ‘monetary equilibrium’, whose maintenance is through both suitable characteristic production operations and by appropriate financial-monetary operations as well.